Need to address digital divide - Aminudin, Rabi'ah; Jamaiudin, Norhaslinda; Abdul Hamid, Rohana; Mohamad Shukri, Syaza Farhana; Lee, Pei May (2020)
THE Covid-19 outbreak has affected the lives of individuals in many different ways. United Nations secretary-general Antonio Guterres has called the pandemic the world’s “greatest test since World War II”. It has resulted in increased government control, shrinking economies – and booming technology.Governments around the world have employed various methods to stop the spread of Covid-19, including imposing movement restriction orders, shutting down economies and enforcing strict social regulations. Malaysia, of course, has had different movement control order (MCO) phases beginning on March 18, with the latest being the recovery MCO, which is scheduled to end on Aug 31.